KREDIBILITAS KEPEMIMPINAN KEPALA MADRASAH DALAM PERSPEKTIF PENDIDIKAN ISLAM: ANALISIS KONSEPTUAL - Mashuri, Mashuri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The credibility of madrasah principals’ leadership is a strategic aspect in efforts to improve the quality of Islamic education, especially amid the challenges of modernization and declining trust in educational institutions. This study aims to examine the concept of leadership credibility and reconstruct it from an Islamic education perspective through a conceptual approach. The method used is qualitative research with a library research and conceptual analysis design, utilizing primary data sources such as the Qur’an and Hadith as well as secondary sources from books and scientific articles. The analytical approach integrates a normative-theological perspective with modern leadership theory. The results indicate that the leadership credibility of madrasah principals is built upon four main dimensions: moral integrity, professional competence, behavioral consistency, and the ability to build trust. From an Islamic perspective, these dimensions are reinforced by the values of siddiq (honesty), amanah (responsibility), tabligh (effective communication), and fathanah (wisdom), which provide an ethical and spiritual foundation for leadership practice. These findings confirm that leadership credibility in Islamic education is not merely managerial in nature but also encompasses normative and theological dimensions. The implications of this research highlight the importance of integrating Islamic values into madrasah leadership development to produce credible, integrity-driven leaders who are also. Kaywords: Educational leadership, leadership credibility, Islamic education, madrasah principals, Islamic values